Novel molding technique for ECAP process and effects on hardness of AA7075 - SAMUR, RAMAZAN (My University, 2014)
In this study, a novel Equal channel angular pressing (ECAP) die which named "Hexa die", designed and manufactured in order to reduce process duration and eliminate manual sample rotation problems. For this reason, the surfaces of die was machined to get the cylindrical channels be able to extract out of ECAP samples. These channels provide 100% accuracy for angular routes for cylindrical samples. Experiments are carried out with the same sample materials (AA7075) at a constant temperature (210°C) and "C" rotation. In the study, process time scenarios for traditional and novel Hexa die techniques have been compared in a theoretical time table. It has been shown that Hexa die has crucial time advantages in order to eliminating the old die process steps such as cooling and reheating time, disassembly and re-assembly of the dies, manually rotation of samples and many of others. And finally ECAP'ed samples hardness have been measured.
Keywords: Aluminum, hardness; Deformation; ECAP; Hexa die; Molding